The challenge of stickiness in knowledge transfer among ICT firms in Malaysian Technology Parks - Mhd. Sarif, Suhaimi; Cook, Ian; Joseph, Richard; Yusof, Ismail (2010)
The study examines knowledge transfer between firms by using the concept of stickiness to conceptualise problems with knowledge transfer. The concept of stickiness is sub-divided into “macro” and “micro” levels stickiness. As for “macro” level stickiness, the study uses literature in the field of innovation studies, in which governments have been identified as major contributors to macro level stickiness. The study uses literature in the economics of knowledge and evolutionary economics to develop the concept of “micro” level stickiness, which refers to firms‟ contributions to stickiness. Four factors are used to examine micro stickiness: transfer mechanisms, types of transfer, knowledge barriers, and transfer contexts. After explaining the concept of stickiness and providing a background to technology parks policy, the study examines the perceptions of a variety of informants of stickiness in knowledge transfer among ICT firms in Malaysian technology parks. The study approached seven (out of eleven) Malaysian technology parks, over a period of three months in 2005 (May-July 2005) and a month in 2007 (August 2007). It interviewed fifty (50) informants, who included policy makers, government officers, and executives of ICT firms in Malaysian technology parks. With respect to “macro” level stickiness, policy makers and government confirmed that the government cannot exclude previous policy documents that contained three major elements: national unity, foreign direct investment and sound economic growth to formulate policy for Malaysian technology parks, which does not solely encourage knowledge transfer because the policy documents permitted short term profit taking by ICT firms. With respect to “micro” level stickiness, the results suggest that transfer mechanisms, types of transfer, knowledge barriers, and transfer contexts are costly; thus, impede ICT firms from participating actively in knowledge transfer between ICT firms. This study suggests that the government and ICT firms should work closely to facilitate knowledge transfer between ICT firms in Malaysian technology parks.